INFLUENCE OF SCHOOL PLANT PLANNING AND SCHOOL COMMUNITY RELATIONSHIP ON PRINCIPALS’ EFFECTIVENESS IN SECONDARY SCHOOL ADMINISTRATION IN ENUGU STATE - Chukwu, Peter Ndubuisi; Ishiwu, Obianuju Florence; Nwobodo, Patience (Journal of Continuing and Development Education, 2023)
The study investigated the Influence of school plant planning and school community relationship on Principals’ Effectiveness in Secondary School Administration in Enugu State. Two research questions guided the study while two null hypotheses were tested at .05 level of significance. The study adopted descriptive survey research design. This study was conducted in Enugu State. In this study, the population was 8816 respondents (295 principals and 8521 teachers). The sample for the study was 1147 respondents which comprised 295 principals and 852 teachers. The sample size was drawn using stratified and proportionate sampling techniques. The instrument for data collection for this study was structured questionnaire titled “Influence of School Plant Planning and School Community Relationship on Principals’ Effectiveness in Secondary School Administration Questionnaire (ISPPSCRPESSAQ). The instrument was validated by three research experts. To ascertain the internal consistency of the instrument, the researcher made use of Cronbach Alpha approach. The reliability coefficients for the various clusters are: Cluster A is 0.80; and Cluster B is 0.79. The overall reliability coefficient of the instrument is 0.80 which makes the instrument reliable and considered appropriate for data collection for the study. Mean scores and standard deviation were used to answer the research questions, while t-test statistic was used to test the hypotheses. The findings of the study revealed that school plant planning and school community relationship influences principals’ effectiveness in secondary school administration to a great extent in secondary schools in Enugu State. Based on the findings of the study, it was recommended among others that School management should provide clear and appropriate measures for managing school plants